Enhancing creativity in genetics using three teaching strategies-based TPACK model - Erni Angraini; Siti Zubaidah; Susanto, Hendra; Omar, Noritah (Modestum, 2022)
Several studies show that the creativity of science students in Indonesia is still low and needs to be empowered and improved. One of the subjects considered difficult by students is genetics because it is abstract and complex. Therefore, educators try technological, pedagogical, and content knowledge (TPACK) model with different strategies. This study aims to analyze and describe the effect of active learning based on the TPACK model with three teaching strategies, namely problem-based learning (PBL), reading, questioning, and answering (RQA), and PBL-RQA, on student creativity in the genetics course at three classes. The research design used was a pre-test-post-test three treatment design. Several teaching strategies used in active learning based on the TPACK model in the genetics course are PBL, RQA, and a combination of PBL-RQA. The research was conducted for one semester. Data was collected through pre- and post-test in the form of description questions distributed through Google Forms. The results showed that the three active learning classes based on the TPACK model have the potential to increase student creativity. The three classes did not differ significantly in increasing student creativity. The three classes have their respective advantages, so educators can choose between the three strategies used by considering the characteristics of students. The three TPACK-based active learning can be used as recommendations in designing the learning process. Educators can also choose the three TPACK-based active learning to empower and increase student creativity.